2021
DOI: 10.3390/jpm11050420
|View full text |Cite
|
Sign up to set email alerts
|

Lincp21-RNA as Predictive Response Marker for Preoperative Chemoradiotherapy in Rectal Cancer

Abstract: Preoperative chemoradiotherapy (CRT) is a standard treatment for locally advanced rectal cancer (RC) patients, but its use in non-responders can be associated with increased toxicities and resection delay. LincRNA-p21 is a long non-coding RNA involved in the p53 pathway and angiogenesis regulation. We aimed to study whether lincRNA-p21 expression levels can act as a predictive biomarker for neoadjuvant CRT response. We analyzed RNAs from pretreatment biopsies from 70 RC patients treated with preoperative CRT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Recent studies found that lincRNA-p21 can inhibit bladder cancer proliferation by negatively regulating glutaminase, glutamate, and α-ketoglutarate expression ( Benitez et al, 2021 ; Scholda et al, 2023 ). Overexpression of glutaminase rescued inhibitory nature of lincRNA-p21 on bladder cancer survival.…”
Section: Non-coding Rna and Mitochondrial Metabolismmentioning
confidence: 99%
“…Recent studies found that lincRNA-p21 can inhibit bladder cancer proliferation by negatively regulating glutaminase, glutamate, and α-ketoglutarate expression ( Benitez et al, 2021 ; Scholda et al, 2023 ). Overexpression of glutaminase rescued inhibitory nature of lincRNA-p21 on bladder cancer survival.…”
Section: Non-coding Rna and Mitochondrial Metabolismmentioning
confidence: 99%
“…Long noncoding RNA (lncRNA) is a special type of RNA that is >200 nucleotides in length and does not directly code for proteins. Long intergenic noncoding RNA is a subtype of lncRNA [64]. lncRNA has recently attracted the attention of researchers, as progress in technology has allowed a more comprehensive understanding of molecular biology.…”
Section: Long Noncoding Rna (Lncrna)mentioning
confidence: 99%
“…Furthermore, they showed that overexpression of LINC00909 contributed to resistance to radiation and 5-FU in vitro and in vivo and was therefore suggested as a potential novel target that could strengthen the response to nCRT. More recently, Benitez et al [64] Table 3. miRNA biomarkers investigated for their ability to predict radiation-based therapy responses in RC patients.…”
Section: Long Noncoding Rna (Lncrna)mentioning
confidence: 99%
“…For instance, Ferrando et al 24 screened three effective lncRNAs to predict NCRT response in LARC patients. Benitez et al 25 identified the Lincp21-RNA to be associated with NCRT response in LARC patients. However, there are only limited studies on lncRNAs associated with NCRT resistance.…”
Section: Introductionmentioning
confidence: 99%